Development and analysis of novel six-lobe helical rotors for hydrogen fuel cell vehicle roots blowers. (26th August 2021) - Li, Dantong; He, Zhilong; Sun, Shizhong; Wang, Chuang; Chen, Wenqing; Xing, Ziwen
Abstract: This paper suggests a novel six-lobe Roots profile to improve the performance of Roots blowers in hydrogen fuel cell vehicles. Mathematical models for rotor profile generation and geometric characteristics are established. A working process simulation model for Roots blowers is developed based on the lumped parameter method and is verified by experimental results. The key profile parameters are discussed and optimized in views of geometric and thermodynamic performance. Case studies are conducted to reveal the detailed performance map difference between several design cases. Results show that a trade-off exists between the rotor cavity volume and adiabatic indicated efficiency for Roots blowers. The proposed profile broadens the design space of rotors in tooth height and achieves a flexible adjustment for the leakage through the blow-hole and contact line. As a consequence, compared to conventional Roots profiles, the proposed rotor profile achieves higher adiabatic indicated efficiency under the same rotor cavity volume. Graphical abstract: Image 1 Highlights: A novel six-lobe rotor profile is presented for Roots blowers in HFCV applications. Mathematical models for profile generation and geometric constraints are given. Models for geometric characteristics and working process simulation are established. The performance of the proposed Roots blowers is discussed comprehensively. A trade-off exists between rotor cavity volume and adiabatic indicated efficiency.